2022
DOI: 10.1155/2022/8694462
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Enhances Neuroplasticity by Regulating the Orexin A-Mediated cAMP/PKA/CREB Signaling Pathway in Senescence-Accelerated Mouse Prone 8 (SAMP8) Mice

Abstract: Learning and memory disorders and decreased neuroplasticity are the main clinical manifestations of age-induced cognitive dysfunction. Orexin A (OxA) has been reported to show abnormally elevated expression in the cerebrospinal fluid (CSF) of patients with Alzheimer’s disease (AD) and to be associated with cognitive impairment. Here, we further assessed whether the excitatory neurotransmitter OxA is involved in neuroplasticity and cognitive function in senescence-accelerated mouse prone 8 (SAMP8) mice. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Activation of the cAMP pathways can ultimately lead to activation of cAMP response element binding protein (CREB) to facilitate transcription of CRE-dependent genes. Traditional Chinese medicine therapy enhances neuroplasticity in SAMP8 mice by regulating the cAMP/PKA/CREB signaling pathway, thus improving cognitive function [33]. Whereas calcium signaling is involved in neurotransmitter release, synaptic plasticity, gene expression and other important neuronal functions [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the cAMP pathways can ultimately lead to activation of cAMP response element binding protein (CREB) to facilitate transcription of CRE-dependent genes. Traditional Chinese medicine therapy enhances neuroplasticity in SAMP8 mice by regulating the cAMP/PKA/CREB signaling pathway, thus improving cognitive function [33]. Whereas calcium signaling is involved in neurotransmitter release, synaptic plasticity, gene expression and other important neuronal functions [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Orexin A-RNAi adenovirus was utilized to silence the orexin gene, simulating the abovementioned consequences of EA. It is hypothesized that 10 Hz EA therapy alters glutamatergic synaptic plasticity mediated by cAMP/PKA/CREB by decreasing cerebrospinal fluid Orexin A levels [ 127 ]. Dopamine (DA) and norepinephrine (NE) and their receptors may also play important roles in synaptic plasticity.…”
Section: Methodsmentioning
confidence: 99%
“…2-VO rats MA "Baihui" (GV20), "Zusanli" (ST36) [94] Row twist compensation method (<90 °, >120 times/min, 30 s), once a day, 6 days of treatment, 1 day of rest, a total treatment of 12 times SAMP8 mice MA "Danzhong" (CV17), "Zhongwan" (CV12), "Qihai" (CV6) [36] Twisting reinforcing manipulation method, 1 time/d, 15 d, and suspended only on day 7 APP/PS1 mice EA "Baihui" (GV20), "Yongquan" (KI1) [41] 2 ~3 mm, "Baihui": Flat stab, "Yongquan": Straight stab, density wave, 1 Hz/50 Hz, 0.5 mA, 15 min/d, 3 times/week, 6 weeks SAMP8 mice EA "Baihui" (GV20), "Zusanli" (ST36) [64] 3 mm, 1 mA, 10 Hz, 30 min/d, 14 days D-galactose-treated rats EA "Baihui" (GV20), "Shenshu" (BL23) [65] "Baihui": Inserted 15 °obliquely, 2 mm. "Shenshu": Inserted perpendicularly, 4-6 mm.…”
Section: -Vo Rats Eamentioning
confidence: 99%
“…Wang et al [ 63 ] found that “olfactory three needle” at “Yintang” (GV29), bilateral “Yingxiang” (LI20) can activate the PI3K-AKT signaling pathway, upregulate the expression of PSD-95, SYN, and GAP43 proteins, improve synaptic plasticity in A β 1-42-treated rats, reduce apoptosis, and alleviate memory impairment. In addition, the study by Hou et al [ 64 ] showed that EA at “Baihui” (GV20), bilateral “Zusanli” (ST36) could improve the memory impairment in SAMP8 mice, and that its mechanism was related to activation of cAMP/PKA/CREB signaling pathway and enhancing synaptic plasticity of hippocampal neurons. Similarly, acupuncture at the corresponding acupoints can inhibit GSK3 β /mTOR in d -galactose-treated rats [ 65 ] and the AMPK/eEF2K/eEF2 [ 66 ] and RhoA/ROCK signaling pathways in SAMP8 mice to promote synaptic plasticity, thereby improving memory impairment [ 67 ].…”
Section: Potential Mechanisms Underlying the Effects Of Acupuncture O...mentioning
confidence: 99%
See 1 more Smart Citation